Effects of modified atmosphere, anti‐browning treatments and ultrasound on the polyphenolic stability, antioxidant capacity and microbial growth in fresh‐cut apples. Issue 5 (18th January 2017) - Putnik, Predrag; Bursać Kovačević, Danijela; Herceg, Korina; Pavkov, Ivan; Zorić, Zoran; Levaj, Branka
Abstract: This study addressed the changes in polyphenolic stability and antioxidant capacity in fresh‐cut apples packaged in modified atmosphere (MAP) as a result of (i) minimal processing parameters (type of cultivar, anti‐browning treatments, and the length of storage); (ii) superficial browning; (iii) ultrasound treatment; and (iv) microbial growth during storage at 4 °C for 14 days. Studied cultivars were Cripps Pink and Golden Delicious. Anti‐browning agents were ascorbic with citric acid and sole Ca‐ascorbate that were both combined with the ultrasound. Identified phenolic compounds in all samples were chlorogenic and p ‐coumaroylquinic acid, quercetin, epicatechin, and phloridzin. Cripps Pink was richer on flavonoids and had the higher antioxidant capacity than Golden Delicious. Application of any anti‐browning treatments did not influence quantities of phenolic compounds, but they showed an improved antioxidant capacity in comparison with untreated samples. Phenolic compounds were stable and antioxidant capacity decreased during storage. Microbial growth had no association with the majority of phenolic compounds (except epicatechin), where it was possible that microorganisms oxidized epicatechin to quercetin together with apple respiratory processes. Practical applications: Fresh‐cut production represents large portion of the international food markets as consumers increasingly demand ready‐to‐eat products. However, these products have a very short shelf‐life with strong impacts on economic gains from such production. Modified atmosphere packaging (MAP) is a very popular industrial preservation technique for prolonging freshness of ready‐to‐eat apples and other foods. Polyphenolics naturally present in apples have various health benefits and favorable influence on nutritive value. Currently, there is a scarcity of available data that simultaneously associates changes in polyphenolic content with minimal processing; apple respiration; storage and superficial browning. This type of data has both, economic and nutritive value for the fresh‐cut production as it is associated with extension of the shelf‐life, plus it is directly related with the superficial browning in this perishable produce.